Answer:
answer : B
Step-by-step explanation:
( x + 7) (3x -2) = 3x² - 2x +21x -14
( x + 7) (3x -2) = 3x²+19x -14
Answer:
I do not understand the question
Step-by-step explanation:
I do not understand the question. Perhaps you can add a picture to clearify?
Answer:
y = - 3x² - 24x - 60
Step-by-step explanation:
The equation of a parabola in vertex form is
y = a(x - h)² + k
where (h, k) are the coordinates of the vertex and a is a multiplier
Here (h, k) = (- 4, - 12 ), thus
y = a(x + 4)² - 12
To calculate a substitute (- 7, - 39) into the equation
- 39 = a(- 7 + 4)² - 12 ( add 12 to both sides )
- 27 = 9a ( divide both sides by 9 )
- 3 = a
y = - 3(x + 4)² - 12 ← in vertex form
Expand (x + 4)²
y = - 3(x² + 8x + 16) - 12
= - 3x² - 24x - 48 - 12
y = - 3x² - 24x - 60 ← in standard form
= - 3(x²
Answer:
39 degrees.
Step-by-step explanation:
We want an angle x such that 0 < x < 360 and angle x is coterminal with an angle of measure 399 degrees.
so x = 399 - 360 = 39 degrees